2002
DOI: 10.5194/npg-9-497-2002
|View full text |Cite
|
Sign up to set email alerts
|

On the problem of optimal approximation of the four-wave kinetic integral

Abstract: Abstract. The problem of optimization of analytical and numerical approximations of Hasselmann's nonlinear kinetic integral is discussed in general form. Considering the general expression for the kinetic integral, a principle to obtain the optimal approximation is formulated. From this consideration it follows that the most well-accepted approximations, such as Discrete Interaction Approximation (DIA) (Hasselmann et al., 1985), Reduced Integration Approximation (RIA) (Lin and Perry, 1999), and the Diffusion A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 18 publications
0
59
0
1
Order By: Relevance
“…However, it is yet unclear that the increase in computational effort is warranted given the uncertainty in the other source terms. A balance must be found between the cost of the computation and its accuracy (e.g., Polnikov and Farina 2002).…”
Section: B Models' Efficiencymentioning
confidence: 99%
“…However, it is yet unclear that the increase in computational effort is warranted given the uncertainty in the other source terms. A balance must be found between the cost of the computation and its accuracy (e.g., Polnikov and Farina 2002).…”
Section: B Models' Efficiencymentioning
confidence: 99%
“…Still, a number of attempts have been made to intercompare different computational methods. Lavrenov (2001 (Polnikov and Farina, 2002;Polnikov, 2003). Using a certain definition of the error measure, it was shown that the DIA approximation is the best one among some other theoretical approximations: the diffusion approximation (Zakharov and Pushkarev, 1999) and the reduced integration approximation (Lin and Perrie, 1999).…”
Section: Inter-comparison Of Computational Methodsmentioning
confidence: 99%
“…Komatsu (1996) (referred to Hashimoto et al, 2002) developed the SRIAM, which is a multiple DIA based on the exact RIAM method. Polnikov and Farina (2002) proposed a version of the fast DIA, which doubles the speed of calculations without loss of accuracy.…”
Section: Development In Computational Methodsmentioning
confidence: 99%
“…
Abstract.A lot of discrete configurations for the fourwave nonlinear interaction processes have been calculated and tested by the method proposed earlier in the frame of the concept of Fast Discrete Interaction Approximation to the Hasselmann's kinetic integral (Polnikov and Farina, 2002). It was found that there are several simple configurations, which are more efficient than the one proposed originally in Hasselmann et al (1985).
…”
mentioning
confidence: 99%
“…At present, this point is very well elaborated, and the only problem is to find the optimal approximation to the kinetic integral, which has the best balance of accuracy and speed of calculations. This problem was considered in detail in our previous paper (Polnikov and Farina, 2002), where one can find a good list of proper references. 1 On the basis of specially constructed mathematical measures and definitions (which is called PF-methodic), the authors of PF have shown that among different modern approximations of the kinetic integral the best one is the so-called Discrete Interaction Approximation (DIA), proposed in Hasselmann et al (1985).…”
Section: Introductionmentioning
confidence: 99%